Four years of experimental results from the New Mexico ACTS propagation terminal at 20.185 and 27.505 GHz. - Pinder, J.
The Advanced Communications Technology Satellite (ACTS) propagation experiment has collected four years of propagation data at 20.185 and 27.505 GHz. The objective of the experiment is to develop long-term statistics and modeling techniques for predicting atmospheric propagation effects in the Ka band. The experiment includes seven identical earth stations at different locations in North America. Each location is meant to characterize a unique rain region. This paper presents the data collected in White Sands, NM. The data from this site provide an excellent resource for validating rain attenuation models due to its unique arid climate with occasional high rain-rate storms. The seasonal and cumulative four-year attenuation statistics for the 20.2 and 27.5 GHz beacons are presented. The attenuation with respect to clear air (ACA) is compared to five different rain attenuation models and seven different frequency scaling models. The results illustrate how well each model predicts rain attenuation in a desert climate region
Keywords: 20.185 GHz; 27.505 GHz; 4 year; ACTS propagation terminal; Advanced Communications Technology Satellite; New Mexico; North America; SHF; White Sands; Arid climate; Atmospheric propagation effects; Beacons; Clear air; Cumulative four-year attenuation statistics; Desert climate region; Earth stations; Experimental results; Fade statistics; Frequency scaling models; High rain-rate storms; Long-term statistics; Modeling techniques; Propagation data; Rain attenuation models; Rain region; Seasonal attenuation statistics